Crowd Flight in Response to Police Dispersal Techniques: A Momentary Lapse of Reason?. Issue 2 (24th January 2013) - Cocking, Chris; Roach, Jason
Abstract There has been much debate about the use of certain public order policing tactics in Britain in response to the disorder seen in recent years. This paper explored the use of an indiscriminate public order tactic that has received comparatively less attention, that of crowd dispersal techniques. More specifically, the use of police charges (either by mounted police or on foot) and subsequent collective flight was investigated. An interview study was conducted with 20 participants who experienced such charges at protests in English cities. Thematic analysis of the data found that although participants reported fear and initial crowd scattering, these instinctive responses were quickly replaced by more socialised reactions, such as co‐operation with others and an increased sense of collective unity. Furthermore, participants reported greater determination to resist what were considered as illegitimate attacks by the police. This increased collective unity was explained in terms of a shared sense of experience that was similar to that found in previous crowd behaviour research. It was concluded that rather than fragmenting crowds, the tactic of crowd dispersal can unite previously heterogeneous groups to resist further police charges and so may be counter‐productive as a public order policing strategy. Copyright © 2013 John Wiley & Sons, Ltd.